Application of CNT nanofluids in a turbulent flow heat exchanger - Walvekar, Rashmi; Siddiqui, Mohammad Khalid; Ong, SeikSan; Ismail, Ahmad Faris (Taylor & Francis, 2015)
Nanofluids have received much attention since its discovery owing to its enhanced thermal conductivity and heat transfer characteristics which makes them a promising coolant in heat transfer application. In this study, the enhancement in heat transfer of carbon nanotube (CNT) nanofluids under turbulent flow conditions is investigated experimentally. The CNT concentration was varied from 0.051 to 0.085 wt%, respectively. The nanofluid suspension was stabilised by gum arabic through a process of homogenisation and water bath sonication at 25'C. The flow rate of cold fluid (water) is varied from 1.7 to 3 L/min, while flow rate of the hot fluid is varied between 2 and 3.5 L/min. Thermal conductivity, density, and viscosity of the nanofluids are also measured as a function of temperature and CNT concentration. The experimental results were validated with theoretical correlations for turbulent flow available in the literature. Results showed an enhancement in heat transfer between 9% and 67% as a function of temperature and CNT concentration.